DEVELOPMENT AND TRENDS IN THE ART OF BOOK DESIGN OF CONTEMPORARY MAINSTREAM EDITIONS - ZOVIENĖ, DANUTĖ (Knygotyra, 2015)
Book design when it comes to titles with mass print runs, or mainstream titles, is a problem avoided by critical discourse in Lithuania. The art of the book design as a separate field tends to be perceived largely as a branch of graphic art created to illustrate books. There is no research dedicated to aspects as book structure and typography of mass production titles. Art critics prefer to dwell on original illustrations and the author’s book; bibliographers analyze books as objects of material and printing culture. There is no analysis of aesthetic principles that guide Lithuanian book design and the impact of the changes that took place at the turn of the 20th still needs to be established. The changes in the design of contemporary editions are best highlighted by the annual competitions of the Most Beautiful Book. Such competitions have been organized in Lithuania for two decades. The magazine Dailė has been recently giving more attention to the problem: it runs articles on the theme and presents the results of the competition. The purpose of this article is to discuss the emergence of the concept of the “art of the book”, the evolution of its content and its application over the 20th century. The impact of major artistic trends on book design is also analyzed. The information on the design of contemporary titles, on the impact of artistic trends, the trends in book design has been collected mainly from publications in the Russian and English languages. The overview of stylistic evolution of book design leads to the conclusion that different artistic styles have reflected in one way or another on book design and typography. At the turn of the 20th – 21st centuries, in the epoch of Postmodernism, the classical foundations of the art of the book were revisited and redefined. Cosmopolitan nature of art has obliterated numerous national stylistic differences. The design of mass production titles in Lithuania has also experienced the influence of the 20th century artistic trends. Yet manifestations of this impact were less pronounced, belated and intertwined with the local tradition. This was determined not so much by geographical, but by political, social and economic circumstance. The contemporary look of the Lithuanian book was mostly influenced by new production techniques, mainly, by the introduction of desktop printing and the emergence of private printing houses that provide for a higher typographical quality. Mainstream titles published in today’s Lithuania present a far-from-homogeneous picture in terms of design and production quality: alongside with books of high artistic quality there are publications of poor layout and design. Mainstream books do not display any Postmodernist influence. Despite stylistic and commercial changes, the key principles in the construction of the book remain the same. Its appearance is determined by the unity of content, text and visual material.